THE COMPOSITION OF WIRE MESH CATCH OF FISHERMEN IN UJUNG TANJUNG TANAH PUTIH DISTRICT ROKAN HILIR REGENCY RIAU PROVINCE - Hefrafis Hefrafis; Alit Hindri Yani; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT             The study was conducted on July 10th to August 8th, 2019 Rokan River, Ujung Tanjung Tanah Putih District, Rokan Hilir Regency, Riau Province. This study aims to determine the composition of the wire mesh haul operated in the Rokan River in Ujung Tanjung. The method used in this study was a survey method. This study was conducted in one month for eight replications, and 20 units of mesh operated in one arrest operation. Each station was submerged by 10 units of mesh and each mesh was separated in 10 meters. The data obtained were put on tables and graphs and then analyzed descriptively. The mesh used in this study made of the main basic material of wire mesh and the size was 1 cm. The length of the mesh body was 120 cm, the diameter was 35 cm, the diameter of the mouth of the mesh was 11 cm, and the diameter of the exit of the mesh was 8 cm. Main catche, the wire mesh fishing gear during the study were marble goby (Oxyeleotris marmorata) with the catch percentage was 37%, by-cath was baung fish(Mystus nemurus) 6%, giant featherback (Chitala lopis) 14%, forest snakehead (Channa lucius) 2 %, striped snakehead (Channa striata) 8%, giant gourami (Osphronemus gouramy) 5%, catfish (Pangasius polyuranodon) 7%, cyprinid (Osteochilus melanopeleurus) 2%, catfish (Clarias sp) 1%, snakeskin gourami(Tricogaster pectoralis) 13%, Indian glassy fish (Parambasis sp) 6%, fire eel (Mastacembelus erythrotaenia) 1%, and striped wallago catfish (Wallago leeri) 1%. Keywords: Wire Mesh, Catch Composition, Rokan River